Pengaruh E-Service Quality dan Brand Image Terhadap E-Loyalty pada Pengguna Aplikasi Shopee - Kornelius Kurniaman Waruwu; Syafrida Hafni Sahir (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the effect of e-service quality and brand image on e-loyalty of Shopee application users in Kelurahan Pasar Gunungsitoli. In this study using quantitative data analysis methods. The data analysis method used is descriptive statistics and Structural Equation Model (SEM) which is processed through the smart-PLS (partial least square) program. The population of this research is all Shopee application users in Kelurahan Pasar Gunungsitoli. The sampling technique was purposive sampling, the sample size to be used was 140 respondents. From the results of data processing, it is known that the variable e-service quality (X1) has a negative effect on e-loyalty of Shopee application users in Pasar Gunungsitoli village. While Brand image (X2) brand image has a positive and significant effect on e-loyalty of Shopee application users in Pasar Gunungsitoli Village.